Vector-valued modular forms on a three-dimensional ball - Freitag, Eberhard; Salvati Manni, Riccardo (Transactions of the American Mathematical Society, 2019)
In this paper we give a structure theorem for the module of vector valued modular forms in the case of a three dimensional ball with the action of the Picard modular group . The corresponding modular variety of dimension is a copy of the Segre cubic.
Published electronically: December 3, 2018
Gesehen am 29.05.2019